Impact of results-based financing on effective obstetric care coverage: evidence from a quasi-experimental study in Malawi - Brenner, Stephan; Wilhelm, Danielle J.; Nesbitt, Robin C.; Lohmann, Julia; De Allegri, Manuela (BMC health services research, 2018)
Results-based financing (RBF) describes health system approaches addressing both service quality and use. Effective coverage is a metric measuring progress towards universal health coverage (UHC). Although considered a means towards achieving UHC in settings with weak health financing modalities, the impact of RBF on effective coverage has not been explicitly studied.
Gesehen am 14.11.2018